Gender and Russian revolutionary thought in exile - Faith Hillis (Diasporas: Circulations, Migrations, Histoire)
Analyzing the communities created by Russian revolutionaries in European exile between about 1860 and 1910, this paper argues that revolutionary gender regimes played an integral role in the creation and expression of radical politics. In contrast to many studies that approach intellectual history from the perspective of texts and doctrinal debates, this article argues that lived experience – including the experience of defining a new gender order – played a crucial role in shaping abstract intellectual ideas. The paper analyzes revolutionary gender regimes in exile (and how they changed over time) by focusing on the gendered praxis of three revolutionary actors : Vera Figner, Vera Zasulich, and Vladimir Lenin. This approach allows us to identify both consistencies and points of evolution in gender regimes over a considerable span of time.